Hemat (Iqtishād) Perspektif Al-Qur’an : Kerangka Normatif Etika Konsumsi Dalam Frugal Living - Hendrisman; Rahendra Maya (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study aims to analyze the concept of moderation in spending (Iqtishād) in the Qur’an as a foundation for consumption moderation and its relevance to the contemporary phenomenon of frugal living. This research employs a qualitative method with a tafsīr taḥlīlī (analytical exegesis) approach to verses related to consumption ethics, such as QS. Al-Furqān: 67, QS. Al-Isrā’: 29, QS. Al-A‘rāf: 31, and QS. Āli ‘Imrān: 180. The findings indicate that the Qur’an constructs a system of consumption ethics based on balance (Iqtishād), positioned between two extremes: excess (isrāf and tabdhīr) and deficiency (bukhl). The concept of Iqtishād is not merely normative but can also be formulated as a framework for consumption moderation encompassing proportionality, responsibility, and sustainability. In the modern context, frugal living can align with Qur’anic values when situated within the framework of Iqtishād, yet it may deviate if it leads to miserliness or disguised forms of excess. This study contributes to the development of contextual Qur’anic exegesis by proposing Iqtishād as an applicable model of Islamic consumption ethics